PENGARUH PENGGUNAAN MODUL E-LEARNING DALAM SETTING MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION (PBI) TERHADAP PENCAPAIAN KOMPETENSI FISIKA SISWA KELAS X SMAN 3 PADANG - Melia Vivi Ningrum; Hidayati Hidayati; Masril Masril (PILLAR OF PHYSICS EDUCATION, 2017)
Ineffective achievement of student competency in learning physics caused by several factors:Teacher use the textbooks of the school when giving lesson about physics, teacher haven’t used ICT materials yet optimally. Scientific approach hasn’t been optimally applied in learning of physics. Teacher are not enough yet in giving some of problems related about materials before starting the lessons. And then the problems that are explained by teacher don’t have the concrete steps to be solved. The solution which is offered in this research is by using e-learning module in setting learning model Problem Based Instruction (PBI). That is aim to increase the achievement of physics competence for student at class X SMAN 3 Padang. To achieve that purpose, it needs to do a quasy experiment research by using the student at class X MIA SMAN 3 Padang who have been registered for 2016/2017 period as population and the sample chosen with purposive sampling technique. An instrument sheets of observation to competence attitude, post-test is to knowledge competence, and performance assessment for competence skills. The data will be analyzed by a chart for analysis attitude competency, using test equality of two average to knowledge competence and skills competence. Based on the data analysis, it can be concluded that there is an influence from the user of learning module in setting model about PBI learning which is related in increasing competence achievement of physics for student class X SMAN 3 Padang by having 95% as the confidence rate